Practical 1-Methylcyclopropene Technology for Increasing Apple (Malus domestica Borkh) Storability in the Aksu Region - Shuang Zhang; Yuanqing Li; Meijun Du; Xihong Li; Junbo Wang; Zhaojun Ban; Yunhong Jiang (Foods, 2024)
In recent years, Aksu apple has become popular with consumers because of its unique texture and taste. At present, maintaining quality during storage is the key problem with the apples in the Aksu region. 1-Methylcyclopropene (1-MCP) can delay fruit senescence, so is widely used in fruit preservation. However, many factors affect the preservation effect of 1-MCP. The effects of 1-MCP concentration (0 µL·L−1, 1 µL·L−1, 3 µL·L−1, 5 µL·L−1, and 8 µL·L−1) and postharvest application time (0, 1 and 2 d after harvest) on the quality of stored apple were studied. It was found that 1 µL·L−1 1-MCP was more beneficial in improving the quality of stored apples, reduced the respiration intensity and decay rate, increased the fruit firmness and total soluble solid content, and reduced the relative content of ester volatile aroma components. In addition, 1-MCP treatment applied at different postharvest times also affected the sensory quality and flavor of apples. The effect of 1-MCP treatment immediately after harvest was better.